PENERAPAN SISTEM OTOMATISASI RUMAH DENGAN MENGGUNAKAN PERANGKAT ARDUINO - AMBAR TRI HAPSARI; ASWIN FITRIANSYAH (LPPM, 2017)
The purpose of the research is to design home automation applications using arduino devices via the web. The research method used by the researcher is a method of development (development research) is a research method used to produce the product, and test the effectiveness of the product. The design of the application begins with the stages of designing the system first, followed by interface design / display, then coding PHP program and microcontroller. After the application is completed, it is done by testing the accuracy of the program by the experts through simulation using the model / miniature of the house which has 4 lamps and 2 doors, the test result that the accuracy of the application meets the test criteria. This application is easy to use / operate (user friendly) with a simple view (user interface), so that user can easily understand the use of the buttons contained in the main menu of the application. This application can make it easier for users to monitor the situation and control the door and home light directly in their home from anywhere.